(untitled) (REMUNOM, 2025)
Means of transportation are extremely important for getting people around, but they are also widely used to move food, animals, raw materials and various other things. They are of great importance to the economic development of cities and are classified as: Maritime, Land and Air. In Brazil, road transport is the most widely used for transporting various types of cargo, due to various factors, such as reaching a greater number of areas within the country, transportation must be carried out by bodies with closed side guards or with metal screens with mesh divisions. The disadvantage of road transport compared to other forms of transport is its reduced load capacity, which suffers from shrinking investment in improving roads, causing losses or compromising the goods transported, and the fragility of Brazil’s roads contributes to the increase in the price of stocks, in addition to the price of consuming diesel, which causes an increase in freight and vehicle prices. Brazil needs more planning and investment to remedy the difficulties of transport logistics, such investments have helped enormously in the integration between transport, which is the most appropriate way to transport soy and corn, developing the logistical operations of the product in the country, the investment service with the aim of expanding to all modes of Brazilian transport are of extreme importance to stimulate the logistical bottlenecks found, in particular to the foreign market that has been expanding on a large scale in the last 10 years. This study will be carried out in order to obtain information on grain losses in road transportation in the state of Tocantins, using the SURVEY methodology (questionnaire) and applied to grain transportation professionals in the state of Tocantins, in order to find out the reasons that cause such significant losses for the local agro-industry, it is also desired by this study to have an estimated amount of losses caused by transportation logistics.